Introduction to the Special Issue: Assessment and Treatment of Stereotypy. (May 2014) - Rapp, John T.; Lanovaz, Marc J.
Stereotypy is often characterized as repetitious, invariant behavior that generates its own reinforcing consequence. Stereotypy represents a unique treatment challenge, because the consequences produced by stereotypy cannot be directly controlled by the practitioner. Likewise, practitioners have relatively few options for identifying the function of repetitive behavior. Recently, several researchers have been conducting empirical studies to address these issues. This article introduces a special issue presenting some of these recent developments in the assessment and treatment of stereotypy and related behavior.